Acute total occlusion of the unprotected left main coronary artery – patient characteristics and outcomes. (3rd October 2022) - Calvao, J; Braga, M; Brandao, M; Campinas, A; Alexandre, A; Amador, A F; Costa, C; Carvalho, M M; Pinto, R A; Proenca, T; Silva, J C; Pires-Morais, G; et al.
Abstract: Background: Acute total occlusion of the unprotected left main coronary artery (ATOLMCA) is a dramatic entity with very high mortality. Owing to its infrequency, there is limited and inconsistent data regarding this population. Purpose: To describe the clinical presentation, short- and long-term outcomes of patients with ATOLMCA. Methods: This retrospective multicentric cohort study included all patients presenting with acute (<12h) myocardial infarction (MI) due to ATOLMCA (Thrombolysis In Myocardial Infarction - TIMI=0) between January 2008 and December 2020 in three tertiary hospitals. Results: In the period of the study, 11, 036 emergent coronary angiographies were performed in the participating centers, 59 of which were ATOLMCA (0.5%). Mean age of patients at the time of the event was 61.2 (±12.2) years. Seventy-three percent were male. At presentation, 72.9% of patients were in cardiogenic shock, and aborted cardiac arrest occurred in 27.1%. Right dominance was present in all patients except one, who had a balanced dominance. Primary percutaneous coronary intervention (PCI) was performed in 89.8% of the patients, with angiographic success being achieved in 55.6% of the procedures. Overall, the in-hospital mortality rate was 57.6%. Mortality was significantly higher in patients without angiographic criteria for PCI success (87.5 vs 36.7%, p<0.001). Among survivors, 91.7% were still alive at 1-year and 66.7% at 5 years of follow-up. Conclusion: Patients with ATOLMCA have a dismal prognosis. Most patients present with cardiogenic shock, and a significant number develop cardiac arrest during the acute phase. Despite medical care, in-hospital mortality is high. Patients with left dominance may not even reach the hospital. Among survivors, long term outcomes are reasonable. Further studies are needed in order to improve the management and outcomes of patients with ATOLMCA. Funding Acknowledgement: Type of funding sources: None.